1989
DOI: 10.1007/bf00292314
|View full text |Cite
|
Sign up to set email alerts
|

Free proline contents in two different groups of rice mutants resistant to hydroxy-L-proline

Abstract: In four rice (Oryza sativa L.) mutants resistant to hydroxy-L-proline (Hyp), HYP101, HYP203, HYP205 and HYP210, and in their original variety, Nipponbare, free proline and Hyp contents in the seeds and in the 14-day-old seedlings have been determined. The four mutants can be divided into two groups: HYP101 and HYP203 are classified as to recessive gene and the levels of free proline are similar to that of the original variety; the second group includes mutants HYP205 and HYP210 where the Hyp resistance is tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Solid arrows Mutant-specific amplification products. Amplification conditions for each STS marker are described in Table 4 Table 5 cumulates the corresponding free amino acid, while a recessive gene-controlled mutant does not (Mori et al 1989). All of the M 4 lines derived from each of the seven resistant PM lines gave an acceptable fit to a 1:2 ratio of the homozygous resistant for the segregating lines (from c 2 =0.29, 0.75>P>0.50 of PM-7 to c 2 =1.46, 0.25>P>0.10 of PM-6) ( Table 5).…”
Section: Conversion Of Aflps Into Sts Markersmentioning
confidence: 99%
“…Solid arrows Mutant-specific amplification products. Amplification conditions for each STS marker are described in Table 4 Table 5 cumulates the corresponding free amino acid, while a recessive gene-controlled mutant does not (Mori et al 1989). All of the M 4 lines derived from each of the seven resistant PM lines gave an acceptable fit to a 1:2 ratio of the homozygous resistant for the segregating lines (from c 2 =0.29, 0.75>P>0.50 of PM-7 to c 2 =1.46, 0.25>P>0.10 of PM-6) ( Table 5).…”
Section: Conversion Of Aflps Into Sts Markersmentioning
confidence: 99%
“…This approach was first applied to plants by Widholm (1972aWidholm ( , 1972b, who isolated tryptophanproducing lines of tobacco by selecting for resistance to 5-methyltryptophan . Amino acid analogue-resistant mutants which overproduce the specific amino acid have been found in bacteria (Czonka, 1981 ;Sugiura & Kisumi, 1985) as well as plants (Widholm, 1976 ;Kueh & Bright, 1982 ;Van Swaaij et al ., 1986 ;Mori et al ., 1989) . It has been reported that free proline-accumulating cell lines resistant to a proline analogue show increased resistance to stresses such as salt (Riccardi et al ., 1983) and freezing (Van Swaaij et al ., 1986, 1987 .…”
Section: Introductionmentioning
confidence: 99%